2019
DOI: 10.18235/0001758
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Sustainability in the Caribbean: An Econometric Analysis

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license. Following a peer review process, and with previous written consent by the Inter-American Development Bank (IDB), a revised ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
2
9
1
Order By: Relevance
“…Recent studies have produced conflicting results for broad fiscal policy in SIDS. Khadan (2019) finds a pro-cyclical fiscal policy while Cevik and Nanda (2020) find a counter-cyclical fiscal policy (but a procyclical government spending bias) in the Caribbean using a comparable collection of countries across overlapping time periods. On the other hand, several studies have identified evidence for the twin deficits hypothesis in the Euro Area (Checherita-Westphal and Žďárek 2017; Everaert and Jansen 2017) and the Caribbean (Khadan 2019) thus reinforcing the endogeneity concern within this space.…”
Section: Figure 1 Graphical Explanation Of Fiscal Fatigue (Percent Of...mentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies have produced conflicting results for broad fiscal policy in SIDS. Khadan (2019) finds a pro-cyclical fiscal policy while Cevik and Nanda (2020) find a counter-cyclical fiscal policy (but a procyclical government spending bias) in the Caribbean using a comparable collection of countries across overlapping time periods. On the other hand, several studies have identified evidence for the twin deficits hypothesis in the Euro Area (Checherita-Westphal and Žďárek 2017; Everaert and Jansen 2017) and the Caribbean (Khadan 2019) thus reinforcing the endogeneity concern within this space.…”
Section: Figure 1 Graphical Explanation Of Fiscal Fatigue (Percent Of...mentioning
confidence: 98%
“…For example, policy makers take into account both the last period's debt levels as well as the historical primary balance when setting in place their current target for the primary balance. There is evidence of strong persistence of primary balances in the Caribbean (Khadan 2019;Cevik and Nanda 2020), and the Euro Area (Checherita-Westphal and Žďárek 2017; Everaert and Jansen 2017).…”
Section: Figure 1 Graphical Explanation Of Fiscal Fatigue (Percent Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies tend to reflect fiscal behavior in large Latin American countries rather than small island states in the Caribbean. A few studies focusing on Latin America and the Caribbean obtain evidence of weak fiscal policy response to an increase in the debt-to-GDP ratio (Kufa, Pellechio, and Rizavi, 2003;Alberola and Montero, 2006;SELA, 2013;Campo-Robledo and Melo-Velandia, 2015;Khadan, 2019;Kemoe and Lonkeng, 2020). Similarly, analyzing the cyclical stance of fiscal policy in Latin America and the Caribbean, Daude, Melguizo, and Neut (2011), Klemm (2014) and Alberola and others (2016) find that fiscal policy is procyclical on average.…”
Section: Related Literaturementioning
confidence: 99%
“…Real GDP growth has returned, although it is still lower than the pre-crisis level, but fiscal imbalances and high debt levels continue to present challenges for some countries. Recent evidence from an intertemporal budget constraint and fiscal reaction functions also suggest that fiscal sustainability in the region has been weak (Khadan, 2019). Some countries, such as Barbados and Jamaica, are undertaking reform programs with the support of the International Monetary Fund (IMF), while others, such as Suriname and Trinidad and Tobago, are pursuing home-grown reform programs to address their respective macroeconomic challenges.…”
Section: Introductionmentioning
confidence: 99%